1992
DOI: 10.1017/s0959269500001289
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of second language development in French immersion

Abstract: In this cross-sectional study of the a acquisition of French by English-speaking immersion students in Ontario, Canada, patterns of second language development are examined with particular reference to verbs. The analysis focuses on second language production data from interviews with 36 early immersion students at three different gradr levels, along with comparison data from a group of late immersion students and two groups of native French speakers. The study documents the learners' well-developed ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0
23

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 11 publications
7
77
0
23
Order By: Relevance
“…Harley and King (1989) found that, compared to native speakers of French of the same age, L2 learners of French in an immersion program underused derived verbs such as affoler and encercler, while Harley (1992) noted their underuse of productive prefixes such re-for expressing the notion of doing something again (e.g., saying dormir encore instead of the more idiomatic se rendormir to express the idea of going back to sleep). These findings were explained in the light of observational research that revealed considerable emphasis in immersion classrooms on learning the meaning of difficult words but with little attention drawn to the structural properties words and how the productive use of affixes can generate many new words (Allen, Swain, Harley, & Cummins, 1990).…”
Section: Why Focus On Derivational Morphology?mentioning
confidence: 99%
“…Harley and King (1989) found that, compared to native speakers of French of the same age, L2 learners of French in an immersion program underused derived verbs such as affoler and encercler, while Harley (1992) noted their underuse of productive prefixes such re-for expressing the notion of doing something again (e.g., saying dormir encore instead of the more idiomatic se rendormir to express the idea of going back to sleep). These findings were explained in the light of observational research that revealed considerable emphasis in immersion classrooms on learning the meaning of difficult words but with little attention drawn to the structural properties words and how the productive use of affixes can generate many new words (Allen, Swain, Harley, & Cummins, 1990).…”
Section: Why Focus On Derivational Morphology?mentioning
confidence: 99%
“…Cesétudes, dont le lecteur peut trouver un exemple dans Harley (1992), ont constaté que si lesélèves d'immersion ont une bonne maîtrise du français parlé, elle est 'moins que native'. On observe notamment dans leur discours oral un nombre non négligeable d'erreurs récurrentes.…”
Section: Bref Ré Sumé Des Objectifs De Not Re P Roj Et De Re C H E Rcheunclassified
“…IMP marking began with states spreading next to other verb classes while PC had an early strong association with achievements, followed respectively by accomplishments, activities and sates. As in Harley (1992), IMP was also found to be lexically restricted to some durative verbs (Fan 2005). Kaplan (1987) conducted an error analysis in a study on patterns of development of PC and IMP acquisition by freshman and sophomore learners of French at university.…”
Section: Discourse Hypothesismentioning
confidence: 86%
“…Thus the ESF project in which the acquisition of temporality by immigrant workers was investigated in target languages such as English, German, Dutch, French and Swedish had some cross-sectional studies beside longitudinal ones (Bhardwaj, Dietrich & Noyau 1988). There are several cross-sectional studies in literature that focused on tense, grammatical and lexical aspect and narrative structure (see, for example, Harley 1992;Hasbún 1995;Kaplan 1987;Salaberry 1999;Schlyter 1990). …”
Section: Methodsmentioning
confidence: 99%